TWO-MIRROR OBJECTIVE WITH PLANE FIELD - N. K. Artioukhina; A. V. Bogatko (Наука и техника)
The paper considers a light-strong anastigmat with plane field that consists of two aspherical mirrors. Calculation of design parameters is given in the paper. Problem concerning protection of image plane against penetration of stray light has been investigated. The objective can be used in space astronomy for investigation of ultra-violet and infrared spectrum regions.